Population balance-enabled model for batch and continuous crystallization processes - Pandit, Ajinkya; Bhambure, Rahul; Ranade, Vivek V. (Chemical Engineering in the Pharmaceutical Industry, 2019)
Crystallization is a critical unit operation in manufacturing of various active pharmaceutical ingredients and drugs. Irrespective of the large-scale use of crystallization in pharmaceutical manufacturing industry, crystallization is still considered as an art. Recently, quality by design (QbD) is gaining industry acceptance as an approach toward development and commercialization of the pharmaceutical drug molecules. In QbD, the unit operations and the process are designed and controlled to deliver specified quality attributes consistently. The proposed chapter is motivated by the necessity of the prediction of crystallization events like onset of the crystallization, nucleation, and growth during crystallization of active pharmaceutical ingredients. The chapter demonstrates the integrated use of population balance modeling framework for developing a fundamental understanding of the kinetic aspects of crystallization and correlating the developed understanding for scale-up and design for the crystallization processes. Efforts are made to discuss the impact of various critical process parameters like metastable zone width, scale effects, and residence time on crystal size during batch and continuous modes with the help of couple of case studies. The presented model and approach will be useful for implementing QbD for crystallizers.